Sustainable River Water Quality Management in Malaysia - Abdullah Al-Mamun; Zaki Zainuddin (International Islamic University Malaysia Engineering Journal, 2013)
Ecological status of Malaysia is not as bad as many other developing nations in the world. However, despite the enforcement of the Environmental Quality Act (EQA) in 1974, the water quality of Malaysian inland water (especially rivers) is following deteriorating trend. The rivers are mainly polluted due to the point and non-point pollution sources. Point sources are monitored and controlled by the Department of Environment (DOE), whereas a significant amount of pollutants is contributed by untreated sullage and storm runoff. Nevertheless, it is not too late to take some bold steps for the effective control of non-point source pollution and untreated sullage discharge, which play significant roles on the status of the rivers. This paper reviews the existing procedures and guidelines related to protection of the river water quality in Malaysia.  There is a good possibility that the sewage and effluent discharge limits in the Environmental Quality Act (EQA) may pose hindrance against achieving good quality water in the rivers as required by the National Water Quality Standards (NWQS). For instance, Ammoniacal Nitrogen (NH3-N) is identified as one of the main pollutants to render many of the rivers polluted but it was not considered in the EQA as a monitoring parameter until the new regulations published in 2009.  Surprisingly, the new regulation for sewage and industrial effluent limits set allowable NH3-N concentration quite high (5 mg/L), which may result in low Water Quality Index (WQI) values for the river water. The water environment is a dynamic system. Periodical review of the monitoring requirements, detecting emerging pollutants in sewage, effluent and runoff, and proper revision of water quality standards are necessary for the management of sustainable water resources in the country. ABSTRAK: Satus ekologi Malaysia tidak seburuk kebanyakan negara membangun lain di dunia. Walaupun Akta Kualiti Alam Sekitar (EQA) dikuatkuasakan pada tahun 1974, kualiti air di pedalaman Malaysia (terutama sungai) semakin merosot. Kebanyakan sungai tercemar akibat pencemaran di punca sumber air dan pencemaran di bukan punca sumber air. Punca sumber air dipantau dan dikawal oleh Jabatan Alam Sekitar (JAS), tetapi sejumlah besar pencemaran adalah sisa yang tidak dirawat dan air larian ribut. Walau bagaimanapun, ia tidak terlambat untuk mengambil beberapa langkah berani untuk mengawal pencemaran di punca sumber air dan sisa tidak dirawat kerana langkah ini memainkan peranan penting bagi kebersihan sungai. Kertas kerja ini mengkaji prosedur dan garis panduan sedia ada berkaitan perlindungan kualiti air sungai di Malaysia. Ada kemungkinan bahawa had kumbahan dan pelepasan efluen dalam Akta Kualiti Alam Sekitar (EQA) boleh menimbulkan halangan terhadap mencapai kualiti air yang baik di dalam sungai seperti yang dikehendaki oleh Piawaian Kualiti Kebangsaan Air (NWQS). Sebagai contoh, Ammoniakal Nitrogen (NH3-N) dikenal pasti sebagai salah satu bahan pencemar utama yang menyebabkan banyak sungai tercemar tetapi ia tidak dianggap sebagai parameter pemantauan dalam EQA hingga peraturan baru diterbitkan pada tahun 2009. Yang menghairankan, peraturan baru menetapkan had efluen perindustrian dan kumbahan dibenarkan pada kepekatan NH3-N yang agak tinggi (5 mg / l), dan ini mungkin menyebabkan nilai Indeks Kualiti Air (WQI) sungai rendah. Persekitaran air adalah sistem dinamik. Menjalankan semakan berkala mengenai syarat pemantauan, mengesan bahan pencemaran di dalam kumbahan, efluen dan aliran, dan semakan piawaian kualiti air yang wajar adalah perlu bagi pengurusan sumber air lestari di negara ini. KEYWORDS:Environmental Quality Act (EQA; point source (PS); non-point source (NPS); sustainable uses; Water Quality Index (WQI)